Outcomes of surgical management for temporomandibular joint ankylosis and pseudoankylosis: a retrospective report of 26 cases - Kocsis, Kristin; Goldschmidt, Stephanie; Thatcher, Graham Paul; Lothamer, Charles; Mestrinho, Lisa Alexandra (Frontiers in Veterinary Science, 2025)
IntroductionTemporomandibular joint ankylosis and pseudoankylosis are uncommon conditions that can lead to devastating consequences. Surgery is the standard of care with different surgical techniques described.ObjectivesThis study compared the outcomes of segmental mandibulectomy (SM), excisional ostectomy (EO), gap arthroplasty (GA), and interpositional arthroplasty (IA) in the surgical management of temporomandibular joint (TMJ) ankylosis and pseudoankylosis in cats and dogs.MethodsCase accrual was requested from the members of the American Veterinary Dental College listserv. The inclusion criteria included a diagnosis of TMJ ankylosis or pseudoankylosis, confirmed either by helical computed tomography (CT) or cone beam computed tomography (CBCT), surgical treatment, and follow-up information of 2 weeks for short-term complications, 3–6 weeks for medium-term complications, and >4 months for long-term complications.ResultsA total of 26 cases (14 cats and 12 dogs) from 10 institutions were included from 2011 to 2024. Surgical treatment outcomes were categorized with a proposed improvement score classification system based on the percent range of motion (ROM) improvement, requirement for revision surgery, and presence of transiente or permanent complications. Excellent, good, and fair outcomes were observed across all procedure types, with no poor outcomes diagnosed. SM resulted in complications in all cases, with no excellent outcomes. Perioperative complications were rare, with only one case of hypothermia reported in a cat. Conversely, the postoperative complication rate was 50% (13/26) and included neuromuscular issues (19.2%; 5/26), malocclusion (26.9%; 7/26), callus formation not requiring surgical revision (3.8%; 1/26), and re-ankylosis requiring surgical revision (15.4%; 4/26). Surgical revision was only required in patients initially treated with SM and GA.ConclusionThis study confirms that excellent outcomes are possible for cats and dogs affected by TMJ ankylosis and pseudoankylosis, and that IA may have postoperative advantages compared to GA and SM.